The application of criterion OBLA in prescribing running endurance training intensity is limited - Usaj, A. (Kinesiologia Slovenica, 2000)
The criterion "onset of blood lactate accumulation" (OBLA) determined in an incremental testing protocol frequently corresponds to maximal lactate steady state phenomenon (maxLAss) during continuous exercise. The aim of this study was to ascertain whether the above-mentioned relationship between both phenomena exists also for intermittent running. Nine healthy runners participated in an incremental testing protocol of repeated 1200 m distances and a training session of 8 x 2000 m, repeated at increased velocities until they were unable to complete the entire session at the required running velocity. Results showed that vOBLA corresponded to maxLAss during training for seven of the runners, but at increased [ LA] = 5.7± 1.2 mmol/l, which is in contrast to LAOBLA = 4 mmol/l. In contrast, for the two remaining runners, [LA] changed in an non-linear manner. Heart rate (HR) reached steady values of 171± 8 b/min, similar as HROBLA= 170± 9 b/min. When the running velocity was increased to vOBLA+0.2 m/s, a dramatic decrease in running distance occurred because of exhaustion. This phenomenon was accompanied by an increase in [ LA]. In contrast to expectations, HR did not increase significantly (175 ± 7 b/min). It may be concluded that OBLA may represent a velocity corresponding to maxLAss for most subjects, however it failed to influence blood [ LA] response during the test and training sufficiently, to be taken as similar and/or predictable. It seems that HROBLA cannot be used as a precise criterion for the determination of HRmaxLAss during training, because it cannot differentiate between vmaxLAss and higher velocity, which effects the early fatigue phenomenon. This means that the OBLA criterion may be a weak method for prescription of running intensity during endurance training.